2018
DOI: 10.18203/2394-6040.ijcmph20183100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition and its determinants in an elderly people in South India

Abstract: Background: The population of elderly people aged ≥60 years is increasing worldwide and is projected to reach 1.5 billion by 2050. In India, the elderly people constitute 8.1% of the total population. Malnutrition is highly prevalent in the elderly population due to various diseases and impairments.Methods: A cross-sectional study was carried out amongst 209 elderly people from February 2018 to April 2018. A questionnaire was used to collect data related to socio-demographic characteristics, Mini Nutritional A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 22 publications
(47 reference statements)
4
19
1
1
Order By: Relevance
“…However, this prevalence was much lower, in studies from Spain and Australia with 13.5 and 16% respectively [2,20]. In addition to those studies, the prevalence of malnutrition was high in the elderly population of India, 32.5% [8], as well as among frail people, 56% [21] and patients with cognitive impairment, 35% [22]. The variation of malnutrition prevalence between these studies can be explained by the differing definitions of malnutrition, non-similar ages of the elderly in various settings such as private households, general practice, communities and institutions, and also the inclusion of individuals from urban or rural areas, subjects with cognitive impairments or frailty.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, this prevalence was much lower, in studies from Spain and Australia with 13.5 and 16% respectively [2,20]. In addition to those studies, the prevalence of malnutrition was high in the elderly population of India, 32.5% [8], as well as among frail people, 56% [21] and patients with cognitive impairment, 35% [22]. The variation of malnutrition prevalence between these studies can be explained by the differing definitions of malnutrition, non-similar ages of the elderly in various settings such as private households, general practice, communities and institutions, and also the inclusion of individuals from urban or rural areas, subjects with cognitive impairments or frailty.…”
Section: Discussionmentioning
confidence: 82%
“…Estimates show that 42% of the elderly residents of institutions and 51% of hospitalized elderly patients in the United States are affected by malnutrition [6]. In Europe and Asia [3,7,8] prevalence of malnutrition varies from 12 to 84%. The prevalence of malnutrition is estimated to be 9.2% among elderly living at home and 21.6% among elderly residents of nursing homes in Iran [7].…”
Section: Introductionmentioning
confidence: 99%
“…The I 2 value indicates that there had large variation of malnutrition in the data set ranging from 2.1% to 60.2%. 30,36 Low rate of malnutrition was reported by Sinha and Mukhopadhyay, Shivraj et al, Gnanaselvam et al, and Konda et al 20,30,35,36,40 In contrast, very high prevalence of elderly malnutrition was reported by Shanbhag, Patel et al, Ghosh et al and Lahiri et al 14,29,25,30 Previous studies in developing countries also showed high prevalence of malnutrition among the elderly as assessed by MNA. A very high prevalence of malnutrition (43.3%) was documented among the Pakistani elderly.…”
Section: Discussionmentioning
confidence: 95%
“…Most of the studies indicated educational status was a crucial risk factor for malnutrition. 9,12,16,20,[23][24][25][26]31 Illiteracy is extremely related to elderly malnutrition and supported by study of Baweja et al 50 Lack of education diminishes the consideration in regards to sound way of life, optimum diet which can attribute to individual nutritional status. Elderly having higher education, owing to their exposure to the outside world, are more aware of personal hygiene, curative health care than that of less educated elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation